Advances in the role of noncoding RNA in temporomandibular arthritis - WU Wenjing; SU Jiansheng (Kouqiang hemian waike zazhi)
Temporomandibular joint osteoarthritis (TMJOA) is a common clinical disease. However, the pathogenesis of TMJOA is still unclear, and there is a lack of effective treatment, bringing great distress to patients. Therefore, it is of great significance to explore the pathogenesis of temporomandibular arthritis and to find effective therapy. Recent studies have shown that noncoding RNA (ncRNA) is involved in regulating the development of TMJOA and has great potential in the diagnosis and treatment of TMJOA. Thus, ncRNA is expected to become new diagnostic marker and therapeutic target. We will review the research progress of noncoding RNA in temporomandibular arthritis.